ANALYSIS OF BEHAVIORAL ASPECT OF ACCOUNTING SYSTEMS - Mufidatur Rohmah; Sri Trisnaningsih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to analyze the behavior of the elements of the accounting system. The success of a company in achieving its goals depends on the accounting system it implements, and human behavior cannot be separated from the success of an accounting system. Behavioral accounting looks at how people interact with accounting systems and how organizations behave. This study uses a literature review research method, with the main objects being books, scientific articles, and other literature. The results of this study indicate that attitudes, emotions, motivation, perceptions, and learning enable the ability of the accounting system to function properly.